Meaning in translation: A model based on translation shifts - Osimo, Bruno (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper proposes a model of meaning-based translation shifts. While the definition of ‘meaning’ may be problematic at best, in practice it is possible to observe what remains in the reception of a message after it has been translated. The author draws on the work of Leuven-Zwart and Torop to build a new model with seven shift categories, each one identified by its influence on various aspects of reception. Examples for each shift category are taken from the first book of the Bible. The findings are channelled into a model for translation meaning.